(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The article aims to reveal the lexical-semantic nature of antonyms in the Uzbek language, considers its types in terms of their structure, their lexical meaning. Also, the typology of the Uzbek and English antonyms is discussed and explained with examples.